Managing urinary incontinence: what works?. (December 2014) - Giarenis, I.; Cardozo, L.
Abstract Urinary incontinence is a common condition, which, although not life-threatening, impairs the health-related quality of life of affected individuals. All women complaining of incontinence require a basic assessment and those with complex or refractory symptoms may benefit from urodynamic studies. Initial treatment includes lifestyle advice, behavioral modifications, bladder retraining and pelvic floor muscle training. For those women with persistent stress urinary incontinence following conservative therapy, surgical management might be considered. The development of the minimally invasive, retropubic, synthetic, mid-urethral sling procedures has revolutionized stress incontinence surgery and reduced the popularity of 'traditional' procedures, such as colposuspension and autologous fascial sling. In an attempt to reduce further the morbidity, transobturator and single-incision slings have been introduced. While antimuscarinic agents are the mainstay of the current medical management of urgency urinary incontinence, a recently developed selective β3-adrenergic receptor agonist (mirabegron) offers an alternative pharmacological option. Modalities such as intravesical botulinum toxin and neuromodulation (peripheral or sacral) are available to women with refractory urgency incontinence. Finally, when all other options have been explored and proven unsuccessful, inappropriate or not feasible, reconstructive surgery or catheter insertion might be considered as a last resort. The aim of this paper is to review conservative, medical and surgical management for urinary incontinence by using the best available evidence in the literature.